2004
DOI: 10.1148/radiol.2323030896
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative US in Patients Undergoing Surgery for Liver Neoplasms: Comparison with MR Imaging

Abstract: Contrast-enhanced MR imaging is as sensitive as intraoperative US in depicting liver lesions before hepatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 15 publications
1
60
0
3
Order By: Relevance
“…In 2004, however, Sahani et al reported the advantages of IOUS with respect to contrast-enhanced MR using a hepatospecific contrast medium. The sensitivity of IOUS and MR was 94.3% and 86.7%, respectively [10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 2004, however, Sahani et al reported the advantages of IOUS with respect to contrast-enhanced MR using a hepatospecific contrast medium. The sensitivity of IOUS and MR was 94.3% and 86.7%, respectively [10].…”
Section: Discussionmentioning
confidence: 98%
“…It has also proved to be valuable in guiding surgical procedures [5,9], particularly minimally invasive laparoscopic techniques, in which direct visual and manual inspection of the affected organs and the retroperitoneum is not possible. However, the role of IOUS has recently been downsized, especially in hospitals where advanced imaging techniques are used preoperatively [10]. The aim of this study was to evaluate the clinical impact of IOUS in the detection of focal liver lesions over the years, comparing it with other imaging modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies 15,19,20 have shown that MRI has a much higher sensitivity than CT in detecting both malignant and nonmalignant lesions. Sahani and colleagues 21 compared the sensitivities of IOUS and MRI and reported that out of 159 histopathology-confirmed lesions analyzed, 12 (7.5%) lesions were seen only with IOUS. However, this finding did not achieve statistical significance, and the authors concluded that MRI was as sensitive as IOUS in detecting liver lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A média de nódulos encontrada na RNM e USIO não mostrou diferença estatística, sugerindo assim, como HAGSPIEGEL et al (11) e SAHANI et al (27) , que a RNM é o método de diagnóstico por imagem pré-operatório que chega mais perto da avaliação intra-operatória pela USIO porém, neste estudo, foram avaliados apenas oito pacientes com RNM e USIO.…”
Section: Discussionunclassified